2013
DOI: 10.2147/rru.s38093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment prostate volume on urinary quality of life following intensity-modulated radiation therapy for localized prostate cancer

Abstract: BackgroundThe aim of this study was to describe the effect of pretreatment prostate volume on urinary quality of life after intensity-modulated radiation therapy (IMRT) for clinically localized prostate cancer.MethodsA total of 368 men treated with prostate IMRT (77.4–81 Gy) were stratified into three gland volume groups, ie, <30 g (group 1), 30–60 g (group 2), and >60 g (group 3). Post-IMRT urinary function was evaluated by National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE) versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recent data from an analysis of 1002 pts treated with high-dose IMRT (86.4Gy) demonstrated that baseline IPSS >15 vs. ≤15 was an independent predictor of grade ≥2 late toxicity [ 26 ]. Hoffman et al demonstrated that men with larger prostate pre-treatment volume have an increased risk of late toxicity [ 37 ], knowing that larger prostate volumes are correlated with higher baseline IPSS [ 38 ]. Nevertheless, no clear threshold value could be identified from the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from an analysis of 1002 pts treated with high-dose IMRT (86.4Gy) demonstrated that baseline IPSS >15 vs. ≤15 was an independent predictor of grade ≥2 late toxicity [ 26 ]. Hoffman et al demonstrated that men with larger prostate pre-treatment volume have an increased risk of late toxicity [ 37 ], knowing that larger prostate volumes are correlated with higher baseline IPSS [ 38 ]. Nevertheless, no clear threshold value could be identified from the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Chevli et al who evaluated 368 patients treated with RT, did not show an association between the volume of the prostate gland (VP) before treatment and urinary toxicity at 1 year [ 23 ]. VP does not appear to be a good indicator of radiotherapy toxicity in patients with or without TURP.…”
Section: Discussionmentioning
confidence: 99%
“…AEs were evaluated using a structured questionnaire covering the side effects reported during EXIST 2 or extension studies and were coded using the Medical Dictionary for Regulatory Activities (MedDRA) preferred term 17,19 . Furthermore, adverse events were continuously monitored in every follow-up visit and graded I-V according to the Common Terminology Criteria for Adverse Events (CTCAE) of the National Cancer Institute version 4.03 via investigator assessment 20 . To assess safety, a complete blood count, urinalysis and the levels of electrolytes (blood urea nitrogen, creatinine, glucose, hepatic enzymes, bilirubin, and serum lipids) were also tested in every patient.…”
Section: Methodsmentioning
confidence: 99%